Dental care for older adults in home health care services - practices, perceived knowledge and challenges among Norwegian dentists and dental hygienists - Marte-Mari; Ewa Alicja Szyszko Hovden; Falk Schwendicke; Vibeke Elise Ansteinsson; Ibrahimu Mdala; Rasa Skudutyte-Rysstad (BMC, 2023)
Abstract Background Providing dental services to dependent older adults might be challenging because of physical and cognitive decline. The present study aimed to explore current practices, knowledge, and experienced challenges related to the treatment of older adults in home health care services (HHCS) among dentists and dental hygienists in Norway. Methods An electronic questionnaire survey was distributed to Norwegian dentists and dental hygienists, inquiring about background characteristics, current practices, self-perceived knowledge, and challenges when providing oral health care for older HHCS patients. Results Four hundred and sixty-six dentists and 244 dental hygienists treating older HHCS patients responded to the survey. The majority were female (n=620; 87.3%) and worked in the public dental service (PDS) (n=639; 90%). When older HHCS adults attended the dental practice, the treatments provided were most frequently aimed at relieving acute oral problems, although dental hygienists reported to focus on improving oral health more often than dentists. Dentists reported to have more self-perceived knowledge than dental hygienists regarding patients with complex treatment needs, cognitive or physical impairment. Exploratory Factor Analysis (EFA) was carried out on the 16 items related to challenges, three factors were extracted and Structural Equation Models (SEMs) were performed. Challenges related to dental care for older HHCS adults were related to time, practical organization and communication. Variation within these categories was associated with sex, graduation year and country, as well as time used per patient and work sector, but not with professional status. Conclusions The results indicate that dental care for older HHCS patients is time-demanding and more often aimed at relieving symptoms than improving oral health. A substantial proportion of dentists and dental hygienists in Norway lack confidence when providing dental care for frail elderly.